2016
DOI: 10.5468/ogs.2016.59.4.328
|View full text |Cite
|
Sign up to set email alerts
|

A female adnexal tumor of probable Wolffian origin showing positive O-6-methylguanine-DNA methyltransferase methylation

Abstract: Female adnexal tumor of probable Wolffian origin (FATWO) is a rare disease entity that arises from the mesonephric duct system. FATWO is different than other gynecological cancers in terms of embryology. Here, we describe the case of a 52-year-old woman with malignant FATWO. The patient underwent explorative laparotomy and surgical staging after a frozen section revealed malignancy. Detailed examination of the pathologic findings were consistent with FATWO. Counseling and further testing were provided to the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 14 publications
0
18
0
2
Order By: Relevance
“…In previous literatures, the recurrence median time was reported at 48 months with a range of 13–96 months . Liver and lung were the most frequent metastatic sites . Heatley once reported that almost 20% of the cases were associated with an adverse outcome .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In previous literatures, the recurrence median time was reported at 48 months with a range of 13–96 months . Liver and lung were the most frequent metastatic sites . Heatley once reported that almost 20% of the cases were associated with an adverse outcome .…”
Section: Discussionmentioning
confidence: 99%
“…Size of the tumor differs in cases ranging from 0.8 to 25 cm in diameter . The typical microscopical features of FATWO include a sieve‐like, diffuse pattern with tubules and cystic structures …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The most commonly used chemotherapy regimen in malignant cases is paclitaxel and carboplatin. 21 Tyrosine kinase inhibitors such as imatinib were also used in some patients with c-Kit þ tumors. 22 However, to determine the effectiveness of this option, collective data are needed from multiple centers.…”
Section: Treatment and Prognosismentioning
confidence: 99%